Peningkatan Kompetensi Guru dalam melaksanakan Pembelajaran Jarak Jauh melalui Workshop - Sonin Jurkarnaen (Journal of Instructional Development Research, 2023)
The purpose of this research is to improve the competence of teachers of SMP Negeri 26 Kota Bekasi in implementing distance learning through workshops. The research subjects were 25 teachers of SMP Negeri 26 Kota Bekasi. The research method used is action research with two cycles. Data collection techniques in the study were obtained from instruments in the form of observation sheets. Observations were made on teacher participation in participating in workshop activities and observation of teacher competence in implementing distance learning. The instrument measures teacher competence in implementing distance learning which consists of six aspects of observation, namely: (1) mastery of information technology, (2) conducting learning, (3) managing interactions, (4) demonstrating special abilities in learning, (5) carrying out assessments learning processes and outcomes, and (6) general impression of the implementation of learning. The results of the research obtained data in the initial conditions, obtained an average score of 2.87 with a success of 57.49%, increased in the first cycle to 3.76 with 75.11% success and increased again in the second cycle to 4.35 with success. 87.01%. Increasing the competence of teachers in implementing distance learning has an impact on improving student learning outcomes which has increased each cycle. The conclusion of this study is that through workshops can improve teacher competence in implementing distance learning at SMP Negeri 26 Kota Bekasi.